A novel method of preparing vanadium-based precursors and their enhancement mechanism in vanadium nitride preparation. Issue 21 (29th April 2022) - Wen, Ailian; Cai, Zhenlei; Zhang, Yimin; Liu, Hong
Abstract : The particle size of the precursor is reduced, while it is easier for N2 to enter the material. A new porous structure appeared and the specific surface area increased, which increases the reaction interface. Abstract : Vanadium nitride is widely used because of its excellent properties. The existing production methods are affected by the problems of complex preparation for the vanadium source, high temperature, and low N content. In this work, a wide range of vanadium solutions were used as the vanadium source to prepare vanadium nitride with high N content. In this work, a novel precursor was prepared by a microwave-assisted precipitation process, and then the vanadium nitride was prepared by reduction and nitridation precursor at 1150 °C. The results show that in the microwave-assisted method, the particle size and structure of the precursor can be adjusted, so that the contact area of the precursor with N2 during the nitridation process becomes larger, the N2 diffusion path becomes shorter, and the formation of vanadium nitride is enhanced. The prepared product has a nitrogen content of 17.67 wt% and is composed of uniform spherical particles. The content of other chemical components and density can achieve the standard requirements specified in VN16. Meanwhile, the thermodynamic analysis showed that the NH3 generated by the thermal decomposition of the precursor can be used directly as a reducing gas to reduce V2 O5, and reduced the emission of polluting gases. It is a feasible method to prepare vanadium nitride by reduction and nitridation.